Concrete for C50 prestressed fabricated box girder and preparation method thereof

By using a concrete formula with low water-cement ratio and high sand rate in prestressed prefabricated box girders, and adding esterified products of graphene oxide and PCE as composite water reducing agents, the weight ratio of natural sand, stone chips, limestone and natural river stone is optimized, and the problem of insufficient resistance to compression deformation is solved, and the compressive resistance and structural stability are significantly improved.

CN119638329APending Publication Date: 2025-03-18天津金隅混凝土有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894997.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The concrete in prestressed prefabricated box girders lacks the ability to resist compression deformation, resulting in stress concentration and structural damage due to incoordinated deformation.

Method used

The concrete formula with low water-cement ratio and high sand rate is used, and the esterification products of graphene oxide and PCE are added as composite water reducing agents. By optimizing the weight ratio of natural sand, stone chips, limestone and natural river stone, the compressive resistance of concrete is improved.

Benefits of technology

The concrete has significantly improved its ability to resist compression deformation, the compressive strength of 7d is not less than 47MPa, and the compressive elastic modulus is not less than 35.2GPa, reducing stress concentration and structural damage caused by the deformation differences of different materials, and extending the service life of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201496860000071
    Figure BDA0005201496860000071
  • Figure BDA0005201496860000091
    Figure BDA0005201496860000091
  • Figure BDA0005201496860000101
    Figure BDA0005201496860000101
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses concrete for a C50 prestressed fabricated box girder and a preparation method of the concrete. The concrete for the C50 prestressed fabricated box girder is prepared from the following raw materials in parts by weight: 400 parts of cement; 150 to 160 parts of water; 100 parts of mineral powder; 30 parts of fly ash; 600 to 700 parts of natural sand; 100 to 150 parts of stone chips; 500 to 600 parts of limestone; 400 to 500 parts of natural river stone; 3-4 parts of a composite water reducing agent; 7-8 parts of other additives; the composite water reducing agent is an esterification product of graphene oxide and PCE, and the other additives comprise a water-retaining agent and an air entraining agent; the preparation method comprises the following steps: mixing the raw materials, and uniformly stirring to obtain the concrete for the C50 prestressed fabricated box girder. The concrete provided by the invention has the advantages of excellent anti-pressure ability and good fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and in particular to a C50 prestressed assembled box girder concrete and a preparation method thereof. Background Art

[0002] Prestressed concrete box girder is a widely used structural form in bridge construction. It applies prestress before the concrete hardens to improve the bearing capacity, crack resistance and durability of the structure. Prestressed concrete box girder usually adopts a box section, which consists of a bottom plate, two side plates and a top plate. This section form provides good bending and torsion resistance. Then, through the tensioning of the steel structure (prestressed steel bars or steel strands), a certain compressive stress is generated before pouring concrete to offset the tensile stress of the box girder during the use stage. Therefore, prestressed concrete box girder has a high bearing capacity, a compact structure, good rigidity, and good seismic resistance. The application of prestress makes the box girder lighter in weight. It is widely used in bridge construction in the fields of highways, railways, urban rail transit, etc., especially in large-span and heavy-load bridges, its advantages are particularly obvious.

[0003] Although the structural characteristics of prestressed concrete box girders bring great advantages to their use, prestressed concrete box girders are one-piece components, which play a key mechanical role in the structure and can directly affect the stiffness and stability of the structure, reducing the degree of deformation of the structure under load to ensure the safety and durability of the structure; in the prestressed concrete box girder structure, the concrete part and the internal steel structure (prestressed steel bars or steel strands) components need to coordinate deformation, and the concrete should play a role in reducing the deformation differences between different materials and weakening the influence of factors such as stress concentration and structural damage caused by uncoordinated deformation on the stability of the overall structure.

[0004] Based on the above problems, and the fact that the hardness and rigidity of steel structures are much greater than those of concrete components and are difficult to adjust, the researchers proposed that the concrete used in prestressed prefabricated box girders can be improved to increase its ability to resist compression deformation, and have conducted many studies on this issue. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a C50 prestressed assembled box girder concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a C50 prestressed assembled box girder concrete, in which the raw materials used include the following components, measured by weight: 400 parts of cement; 150-160 parts of water; 100 parts of mineral powder; 30 parts of fly ash; 600-700 parts of natural sand; 100-150 parts of stone chips; 500-600 parts of limestone; 400-500 parts of natural river stone; 3-4 parts of composite water reducer; 7-8 parts of other admixtures; the composite water reducer is an esterification product of graphene oxide and PCE, and other admixtures include water retaining agent and air entraining agent.

[0007] Specifically, the preparation method of the composite water reducer includes the following steps: firstly dispersing graphene oxide in N,N-dimethylformamide, ultrasonically treating, then adding N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine, mixing evenly for later use, dispersing PCE in N,N-dimethylformamide, slowly dripping into the above-mentioned reserved mixed solution after PCE is completely dissolved, stirring to react at room temperature, filtering to obtain a solid after the reaction is completed, washing with methanol, and drying to obtain a composite water reducer.

[0008] By adopting the above technical solution, the present application firstly controls the water-cement ratio to be between 28.3% and 30.2%, and then controls the ratio of the amount of fine aggregate (natural sand and stone chips) and coarse aggregate (limestone and natural river stone), thereby adjusting the sand rate in the system to 39.8% to 47.9%. Compared with the existing concrete system, the water-cement ratio in the system of the present application is reduced by 2% to 4.5%, and the sand rate is increased by 5% to 10%, thereby effectively improving the workability of the concrete, ensuring the smooth pouring of the concrete, and ensuring the uniformity and density of the concrete structure, reducing the number of pores in the concrete, and reducing the penetration of water and corrosive substances; In addition, the present application adds the esterification product of graphene oxide and PCE (polycarboxylic acid compound) as a composite water reducer, which effectively improves the fluidity of cement slurry and greatly reduces the grain size of hydrates in the system. Although the water-cement ratio in the system is reduced, the concrete of the present application still has good fluidity due to the water-reducing effect of the composite water reducer, and the slump is not less than 150 mm. The composite water reducer also includes a graphene oxide component, which can not only improve its own dispersion in the system and avoid agglomeration after esterification with PCE, but also cooperate with the low water-cement ratio and high sand ratio of the present application to jointly improve the ability of concrete to resist compression deformation.

[0009] In summary, the present application utilizes a low water-cement ratio, a high sand ratio, the addition of graphene oxide, and the combination of natural sand, stone chips, limestone and natural river stones, a variety of reinforcing materials and strictly controlled material ratios to achieve a good synergistic effect. Without affecting the fluidity of the concrete, the ability of the concrete to resist compressive deformation is jointly improved. The 7d compressive strength is not less than 47MPa, and the compressive elastic modulus is not less than 35.2GPa. Applying it to prestressed assembled box girder structures can reduce the deformation differences between different materials and weaken the influence of factors such as stress concentration and structural damage caused by uncoordinated deformation on the overall structural stability.

[0010] Preferably, the weight ratio of the natural sand to stone chips is 680:120.

[0011] By adopting the above technical solution, the present application further controls the weight ratio of natural sand and stone chips to 680:120, at which point the two can play the best synergistic effect, further optimize the pore structure and density of the concrete, and can significantly enhance the overall mechanical properties of the concrete and improve its compressive strength. At the same time, the addition of stone chips can also improve the working performance of concrete, making it easier to construct and reducing segregation during construction. Ultimately, this combination helps to improve the structural stability and durability of prestressed assembled box girders and reduce stress concentration and structural damage caused by deformation differences of different materials.

[0012] Preferably, the weight ratio of the natural sand, limestone and natural river stone is 680:520:(400-500).

[0013] By adopting the above technical solution, the present application further controls the weight ratio of natural sand, limestone and natural river stone, thereby further controlling the sand ratio. At this time, the uniformity and density of the concrete structure are better, the number of internal pores is smaller, and the penetration of moisture and corrosive substances is also weakened. This makes the concrete show better resistance to compression deformation in the application of prestressed assembled box girders, thereby extending the service life of the structure.

[0014] Preferably, the weight ratio of the limestone to the natural river stone is 520:450.

[0015] By adopting the above-mentioned technical scheme, the present application further controls the weight ratio of limestone and natural river stone. At this time, the two can play the best synergistic effect, further optimize the pore structure and density of concrete, can significantly enhance the overall mechanical properties of concrete, improve its compressive strength, can greatly improve the structural stability and durability of prestressed assembled box girders, and reduce stress concentration and structural damage caused by deformation differences of different materials.

[0016] Preferably, the weight ratio of the water retaining agent to the air entraining agent is 10:(1-2).

[0017] By adopting the above technical solution, the present application adds a certain amount of water-retaining agent and air-entraining agent, thereby improving the water retention performance of concrete, reducing water evaporation during construction, improving the internal density of concrete, and enhancing the overall stability of concrete.

[0018] Preferably, the preparation method of PCE comprises the following steps: mixing isopentanol polyoxyethylene ether, acrylic acid, sodium methacrylate sulfonate, an initiator, a chain transfer agent and water, controlling the initial reaction temperature to 13-18°C, stirring the reaction for 3-5 hours, and then adjusting the pH in the system to 6-8 to obtain PCE, wherein the weight ratio of isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylate sulfonate is 1:(2.5-5):(0.2-0.4), and the weight ratio of isopentanol polyoxyethylene ether to the chain transfer agent is 1:(0.14-0.20).

[0019] By adopting the above technical scheme, the present application uses isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylic acid as reaction monomers, and obtains PCE with excellent dispersibility and good water-reducing effect in the system of initiator and chain transfer agent. Adding it to the system can significantly improve the fluidity and slump of cement slurry, promote the close arrangement of calcium sulfonate in the concrete system, and effectively improve the compressive strength of concrete. The initiator in the present application is ammonium persulfate and ascorbic acid in a weight ratio of 12: 1, the chain transfer agent is thioglycolic acid, and the above substances are only exemplified by the present application, and the protection scope of the present application cannot be limited accordingly. Therefore, the initiator and the chain transfer agent are substances that can be reasonably adjusted by technicians in this field according to actual conditions.

[0020] Preferably, in the preparation method of PCE, the weight ratio of prenol polyoxyethylene ether, acrylic acid and sodium methacrylic acid sulfonate is 1:4:0.3.

[0021] By adopting the above technical scheme, the present application strictly controls the weight ratio of isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylate sulfonate. The PCE obtained under this weight ratio has more carboxylic acid groups inside, which can make PCE easier to anchor on the surface of cement particles. The long side chains on PCE can better play a steric hindrance role, improve the fluidity of cement slurry, and thus improve the compressive strength of concrete.

[0022] Preferably, in the preparation method of PCE, the weight ratio of isopentanol polyoxyethylene ether to the chain transfer agent is 1:0.18.

[0023] By adopting the above technical solution, the present application strictly controls the weight ratio of isopentanol polyoxyethylene ether to the chain transfer agent. The PCE obtained under this weight ratio has more carboxylic acid groups inside, which can make the PCE more easily anchored on the surface of cement particles.

[0024] In a second aspect, the present application provides a method for preparing C50 prestressed assembled box girder concrete, comprising the following steps: mixing the raw materials used, and stirring evenly to obtain C50 prestressed assembled box girder concrete.

[0025] By adopting the above technical scheme, the C50 prestressed assembled box girder concrete obtained in this application has no cracks and no color difference on the surface after pouring, and the 7d solid rebound strength can reach more than 90% of the design strength, which has a high use value.

[0026] In summary, this application has the following beneficial technical effects: 1. This application utilizes low water-cement ratio, high sand ratio, addition of graphene oxide, and combination of natural sand, stone chips, limestone and natural river stone, multiple reinforcing materials and strictly controlled material ratios to achieve good synergistic effects. Without affecting the fluidity of concrete, the ability of concrete to resist compressive deformation is jointly improved. The 7d compressive strength is not less than 47MPa, and the compressive elastic modulus is not less than 35.2GPa. When applied to prestressed assembled box girder structures, it can reduce the deformation differences between different materials and weaken the influence of factors such as stress concentration and structural damage caused by uncoordinated deformation on the stability of the overall structure. 2. The present application further controls the weight ratio of natural sand, limestone and natural river stone, thereby further controlling the sand ratio. At this time, the uniformity and density of the concrete structure are better, the number of internal pores is smaller, and the penetration of moisture and corrosive substances is also weakened, which makes the concrete show better anti-compression deformation ability in the application of prestressed assembled box girders, thereby extending the service life of the structure; 3. This application utilizes isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylic acid sulfonate as reaction monomers, and obtains PCE with excellent dispersibility and good water-reducing effect in the system of initiator and chain transfer agent. Adding it into the system can significantly improve the fluidity and slump of cement slurry, promote the close arrangement of calcium sulfonite in the concrete system, and effectively improve the compressive strength of concrete. DETAILED DESCRIPTION

[0027] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Cement was purchased from Tianjin Jinyu Zhenxing Environmental Protection Technology Co., Ltd., model P.O52.5; Natural sand, crushing rate 0.35%, wear rate 0.09%, bulk density 1.72, particle size 3-4.75mm; Mineral powder, density 2.93kg / m 3 , loss on ignition 0.65wt%, particle size 3-4.75mm; Stone chips, wear rate 41%, particle size 3-4.75mm; The particle size of natural river stone is 5-20mm and the bulk density is 150kg / m 3 , specific gravity 2.8, continuous grading; Isoprenoic acid polyoxyethylene ether was purchased from Shandong Zhuoxing Chemical Co., Ltd., with a number average molecular weight of 2400; Ammonium persulfate and thioglycolic acid were purchased from Shanghai MacLean Biochemical Co., Ltd.; Acrylic acid, sodium methacrylic acid sulfonate, and ascorbic acid were purchased from Sinopharm Chemical Reagent Co., Ltd.; Graphene oxide was purchased from Henan Wanying Refractory Material Technology Co., Ltd. with a particle size of 1000 mesh and a grayscale of 50 ppm; N,N-Dicyclohexylcarbodiimide was purchased from Shanghai Yishi Chemical Co., Ltd., CAS No. 538-75-0; 4-Dimethylaminopyridine was purchased from Jiangsu Pules Biotechnology Co., Ltd., CAS No. 1122-58-3; The polycarboxylic acid slump-preventing agent was purchased from Beijing Jinyu Cement Energy Saving Technology Co., Ltd., model JY-TS-2; The water-retaining agent was purchased from Beijing Jinyu Cement Energy Saving Technology Co., Ltd., model JY-BS; The air entraining agent was purchased from Beijing Jinyu Cement Energy Saving Technology Co., Ltd., and its main component was sodium dodecyl sulfate; The particle size of limestone is 5-20mm and the density is 2600kg / m 3 , compressive strength 600MPa, continuous grading; The particle size of fly ash is 40-50um and the bulk density is 1.3g / cm 3 .

[0028] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0029] Preparation Example 1.1 The preparation method of the composite water reducing agent comprises the following steps: 1. Preparation of PCE: Disperse 1 kg of isopentanol polyoxyethylene ether and 0.12 kg of ammonium persulfate in water, stir until the solid is completely dissolved, and use it as liquid A for standby use; disperse 2.5 kg of acrylic acid and 0.4 kg of sodium methyl propylene sulfonate in water, stir evenly and use it as liquid B for standby use; disperse 0.14 kg of thioglycolic acid and 10 g of ascorbic acid in water, stir evenly and use it as liquid C for standby use; add liquid B and liquid C into a metering pump, and pump them into liquid A at a uniform speed within 20 minutes. After the pumping is completed, control the initial temperature of the reaction to 13°C, stir the reaction for 5 hours, and after the reaction is completed, pour the reactants into a beaker and cool to room temperature, then use 30 wt% NaOH solution to adjust the pH in the system to 6-8 to obtain PCE; 2. Preparation of composite water reducing agent: first disperse 5 kg of graphene oxide in N, N-dimethylformamide, ultrasonically treat for 30 min, then add 0.5 kg of N, N-dicyclohexylcarbodiimide and 0.35 kg of 4-dimethylaminopyridine, ultrasonically treat for 30 min, mix well and set aside, disperse 2 kg of PCE prepared in step I in N, N-dimethylformamide, slowly drip into the above-mentioned standby mixed solution after PCE is completely dissolved, stir and react at room temperature for 6 h, filter to obtain solid after the reaction is completed, wash with methanol, and dry to obtain a composite water reducing agent.

[0030] Preparation Example 1.2 The preparation method of the composite water reducing agent comprises the following steps: 1. Preparation of PCE: Disperse 1 kg of isopentanol polyoxyethylene ether and 0.12 kg of ammonium persulfate in water, stir until the solid is completely dissolved, and use it as liquid A for standby use; disperse 5 kg of acrylic acid and 0.2 kg of sodium methyl propylene sulfonate in water, stir evenly and use it as liquid B for standby use; disperse 0.2 kg of thioglycolic acid and 10 g of ascorbic acid in water, stir evenly and use it as liquid C for standby use; add liquid B and liquid C into a metering pump, and pump them into liquid A at a uniform speed within 20 minutes. After the pumping is completed, control the initial reaction temperature to 18°C, stir the reaction for 3 hours, and after the reaction is completed, pour the reactants into a beaker and cool to room temperature, then use 30 wt% NaOH solution to adjust the pH in the system to 6-8 to obtain PCE; 2. Preparation of composite water reducing agent: first disperse 5 kg of graphene oxide in N, N-dimethylformamide, ultrasonically treat for 30 min, then add 0.5 kg of N, N-dicyclohexylcarbodiimide and 0.35 kg of 4-dimethylaminopyridine, ultrasonically treat for 30 min, mix well and set aside, disperse 2 kg of PCE prepared in step I in N, N-dimethylformamide, slowly drip into the above-mentioned standby mixed solution after PCE is completely dissolved, stir and react at room temperature for 6 h, filter to obtain solid after the reaction is completed, wash with methanol, and dry to obtain a composite water reducing agent.

[0031] Preparation Example 1.3 The preparation method of the composite water reducing agent is different from that of Preparation Example 1.1 in that: in step I, the amount of acrylic acid used is 4 kg, the amount of sodium methyl methacrylate sulfonate used is 0.3 kg, and the rest is the same as Preparation Example 1.1.

[0032] Preparation Example 2.1 The preparation method of the composite water reducing agent is different from that of Preparation Example 1.3 in that: in step I, the initial reaction temperature is controlled to be 15°C, the stirring reaction time is 4 hours, and the rest is the same as Preparation Example 1.3.

[0033] Preparation Example 2.2 The preparation method of the composite water reducing agent is different from that of Preparation Example 1.3 in that: in step I, the initial reaction temperature is controlled to be 15° C., the stirring reaction time is 4.5 h, and the rest is the same as Preparation Example 1.3.

[0034] Preparation Example 2.3 The preparation method of the composite water reducing agent is different from that of Preparation Example 1.3 in that: in step I, the initial reaction temperature is controlled to be 14° C., the stirring reaction time is 4 h, and the rest is the same as Preparation Example 1.3.

[0035] Preparation Example 3.1 The preparation method of the composite water reducing agent is different from that of Preparation Example 2.1 in that: in step I, the amount of thioglycolic acid used is 0.15 kg, and the rest is the same as that of Preparation Example 2.1.

[0036] Preparation Example 3.2 The preparation method of the composite water reducing agent is different from that of Preparation Example 2.1 in that: in step I, the amount of thioglycolic acid used is 0.17 kg, and the rest is the same as that of Preparation Example 2.1.

[0037] Preparation Example 3.3 The preparation method of the composite water reducing agent is different from that of Preparation Example 2.1 in that: in step I, the amount of thioglycolic acid used is 0.19 kg, and the rest is the same as that of Preparation Example 2.1.

[0038] Examples 1.1-1.2 A method for preparing concrete for C50 prestressed assembled box beams comprises the following steps: Cement, water, mineral powder, fly ash, natural sand, stone chips, limestone, natural river stone, composite water reducing agent and other admixtures (water retaining agent and air entraining agent) were mixed according to the amounts in Table 1, and stirred at a speed of 80 r / min for 20 min to obtain C50 prestressed assembled box girder concrete.

[0039] Table 1 Component dosage of Examples 1.1-1.3 (kg) Example 2.1 A method for preparing concrete for C50 prestressed assembled box beams, which is different from Example 1.1 in that the amount of natural sand used is 680 kg, the amount of stone chips used is 120 kg, and the rest is the same as Example 1.1.

[0040] Example 2.2 A method for preparing concrete for C50 prestressed assembled box beams, which is different from Example 1.1 in that the amount of natural sand used is 650 kg, the amount of stone chips used is 150 kg, and the rest is the same as Example 1.1.

[0041] Example 3.1 A method for preparing concrete for C50 prestressed assembled box beams, which is different from Example 2.1 in that the amount of limestone used is 520 kg, and the rest is the same as Example 2.1.

[0042] Example 3.2 A method for preparing concrete for C50 prestressed assembled box girders, which is different from Example 2.1 in that the amount of limestone used is 520 kg, the amount of natural river stone used is 400 kg, and the rest is the same as Example 2.1.

[0043] Example 3.3 A method for preparing concrete for C50 prestressed assembled box girders, which is different from Example 2.1 in that the amount of limestone used is 520 kg, the amount of natural river stone used is 450 kg, and the rest is the same as Example 2.1.

[0044] Example 4 A method for preparing concrete for C50 prestressed assembled box girders, which differs from Example 3.3 in that the composite water reducer prepared in Preparation Example 1.1 is replaced by the composite water reducer prepared in Preparation Example 1.3, and the rest is the same as Example 3.3.

[0045] Examples 5.1-5.3 A method for preparing concrete for C50 prestressed assembled box girders, which is different from Example 4 in that the composite water reducing agent prepared in Preparation Example 1.3 is replaced by the composite water reducing agent prepared in Preparation Examples 2.1-2.3 respectively, and the rest is the same as Example 4.

[0046] Examples 6.1-6.3 A method for preparing concrete for C50 prestressed assembled box girders, which differs from Example 5.1 in that the composite water reducing agent prepared in Preparation Example 2.1 is replaced by the composite water reducing agent prepared in Preparation Examples 3.1-3.3 respectively, and the rest is the same as Example 5.1.

[0047] Comparative Example 1.1 The difference from Example 1.1 is that the amount of stone chips is 50 kg, the amount of natural sand is 400 kg, the amount of limestone is 675 kg, and the amount of natural river stone is 675 kg. The rest is the same as Example 1.1.

[0048] Comparative Example 1.2 The difference from Example 1.1 is that the amount of stone chips is 200kg, the amount of natural sand is 900kg, the amount of limestone is 350kg, and the amount of natural river stone is 350kg. The rest is the same as Example 1.1.

[0049] Comparative Example 2 The difference from Example 1.1 is that the composite water reducing agent prepared in Preparation Example 1.1 is completely replaced by the PCE prepared in Step I of Preparation Example 1.1, and the rest is the same as Example 1.1.

[0050] Performance Testing 1. According to the record in GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the compressive strength of the C50 prestressed assembled box girder concrete prepared in the embodiment of the present application and the comparative example under 7d was tested respectively. The specific detection method is as follows: The concrete prepared in the embodiment and the comparative example were respectively made into cubes with a side length of 150 mm as concrete specimens. Each group of concrete specimens consisted of 3 pieces. The concrete specimens were cured for 7 days, and then the compressive strength (MPa) was tested using a pressure testing machine. The pressure loading rate was 0.5-0.8 MPa / s. The average value of each group of 3 test pieces is recorded in Table 2. 2. According to the record in JTG E30-2005 "Testing Procedures for Cement and Cement Concrete in Highway Engineering", the 7d compressive elastic modulus of the C50 prestressed assembled box girder concrete prepared in the embodiment of the present application and the comparative example was tested respectively. The specific detection method is as follows: The concrete prepared in the embodiment and the comparative example was made into a 150mm×150mm×300mm cuboid as a concrete test piece, and each group of concrete test pieces consisted of 3 pieces. The concrete test pieces were cured for 7 days, and then the compressive elastic modulus was tested using a pressure testing machine. First, the pressure of the initial load value was maintained for 60s, and the subsequent 30s was a reading cycle. Then, the pressure was uniformly increased from the initial load value to the maximum load value, and the pressure was increased according to the record in the standard document. The 7d compressive elastic modulus (GPa) was calculated according to the formula in the record, and the average value of each group of 3 test pieces was recorded in Table 2; 3. According to the record in JTG E30-2005 "Test Procedure for Cement and Cement Concrete for Highway Engineering", the slump of the C50 prestressed assembled box girder concrete prepared in the embodiment of the present application and the comparative example was tested respectively. The specific detection method is as follows: a trumpet-shaped slump cone with an upper diameter of 100 mm, a lower diameter of 200 mm, and a height of 300 mm was used to load the concrete into the slump cone three times. After each loading, a tamping hammer was used to evenly hit the cylinder wall from the outside to the inside for 25 times to ensure that the concrete is fully compacted. After the concrete is filled and compacted, the slump cone is lifted vertically upward and moved aside. The concrete mixture will collapse due to its own weight. The height difference between the cylinder height of the slump cone and the highest point of the concrete pile after collapse is measured with a steel ruler, which is the slump value (mm). The average value of each group of 3 test blocks is recorded in Table 2.

[0051] Table 2 Performance test table Data Analysis: As can be seen from Table 2, the C50 prestressed assembled box girder concrete obtained in Examples 1.1-1.2 of the present application has a compressive strength of 47.1-47.3 MPa after 7 days of curing, a compressive elastic modulus of 35.2-35.4 GPa, and a slump of 152-153 mm, which proves that the present application utilizes a low water-cement ratio, a high sand ratio, the addition of graphene oxide, and a variety of reinforcing materials and a strictly controlled material ratio to achieve a good synergistic effect, and jointly improves the ability of concrete to resist compression deformation without affecting the fluidity of concrete; The difference between Example 2.1-2.2 and Example 1.1 is that the present application changes the weight ratio of natural sand and stone chips, and the C50 prestressed assembled box girder concrete obtained in Example 2.1 has improved compressive strength and compressive elastic modulus after 7 days of curing, proving that the present application further controls the weight ratio of natural sand and stone chips to 680:120, which can further optimize the pore structure and density of concrete, significantly enhance the overall mechanical properties of concrete, and improve its compressive strength. At the same time, the addition of stone chips can also improve the working performance of concrete, making it easier to construct and reducing segregation during construction. Ultimately, this combination helps to improve the structural stability and durability of prestressed assembled box girders, and reduce stress concentration and structural damage caused by deformation differences of different materials; The difference between Examples 3.1-3.3 and Example 2.1 is that the present application further optimizes the weight ratio of limestone and natural river stone under the condition of optimizing the weight ratio of natural sand and stone chips. The compressive strength and compressive elastic modulus of the C50 prestressed assembled box girder concrete obtained in Examples 3.1-3.2 after 7 days of curing are improved compared with those in Example 2.1. The compressive strength and compressive elastic modulus of the C50 prestressed assembled box girder concrete obtained in Example 3.3 after 7 days of curing are improved compared with those in Examples 3.1-3.2. This proves that the present application further controls the sand rate and the component ratio inside the coarse aggregate, so that the uniformity and density of the concrete structure are better, the number of internal pores is smaller, and the penetration degree of moisture and corrosive substances is also weakened, which makes the concrete show better resistance to compression deformation in the application of prestressed assembled box girders, greatly improves the structural stability and durability of prestressed assembled box girders, reduces stress concentration and structural damage caused by deformation differences of different materials, and thus extends the service life of the structure; Example 4 is different from Example 3.3 in that the composite water reducer prepared in Preparation Example 1.1 is replaced by the composite water reducer prepared in Preparation Example 1.3 in the present application. At this time, the slump, compressive strength and compressive elastic modulus of the C50 prestressed assembled box girder concrete obtained after 7 days of curing are significantly improved, proving that the present application can make PCE more easily anchored on the surface of cement particles by strictly controlling the weight ratio of isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylic acid sulfonate, and the long side chains on PCE better play a steric hindrance role, thereby improving the fluidity of cement slurry and thus improving the compressive capacity of concrete; The difference between Examples 5.1-5.3 and Example 4 is that the composite water reducing agent prepared in Preparation Example 1.3 is replaced by the composite water reducing agent prepared in Preparation Examples 2.1-2.3 in the present application. At this time, the slump of the C50 prestressed assembled box girder concrete obtained in Example 5.1 is improved, and is the highest among the four groups of examples. The compressive strength and compressive elastic modulus after 7 days of curing are also improved. It is proved that the present application improves the water reducing ability of PCE by strictly controlling the initial reaction temperature and the stirring reaction time in the preparation of PCE, which can further improve the fluidity of cement slurry and improve the compressive capacity of concrete; The difference between Example 6.1-6.3 and Example 5.1 is that the composite water reducer prepared in Preparation Example 3.1 is replaced by the composite water reducer prepared in Preparation Examples 3.1-3.3 in the present application. At this time, the slump of the C50 prestressed assembled box girder concrete obtained in Example 6.1 is improved, and is the highest among the four groups of examples. The compressive strength and compressive elastic modulus after 7 days of curing are also improved, which proves that the present application can make PCE more easily anchored on the surface of cement particles by strictly controlling the weight ratio of isopentanol polyoxyethylene ether to chain transfer agent; The compressive strength and compressive elastic modulus of the C50 prestressed assembled box girder concrete obtained in Comparative Examples 1.1-1.2 after 7 days of curing are much lower than those in Example 1.1, which proves that the present application reasonably adjusts the sand ratio in the system to effectively improve the workability of the concrete, ensure the smooth pouring of the concrete, ensure the uniformity and density of the concrete structure, reduce the number of pores in the concrete, and reduce the penetration of moisture and corrosive substances; The compressive strength and compressive elastic modulus of the C50 prestressed assembled box girder concrete obtained in Comparative Example 2 after 7 days of curing are much lower than those in Example 1.3, which proves that the present application improves the dispersion of the composite water reducer in the system and avoids agglomeration by utilizing graphene oxide and PCE esterification, and at the same time can cooperate with the low water-cement ratio and high sand ratio of the present application to jointly improve the ability of concrete to resist compression deformation.

[0052] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A C50 prestressed assembled box girder concrete, characterized in that: The raw materials used include the following components by weight: 400 parts of cement; 150-160 parts of water; 100 parts of mineral powder; 30 parts of fly ash; 600-700 parts of natural sand; 100-150 parts of stone chips; 500-600 parts of limestone; 400-500 parts of natural river stones; 3-4 parts of composite water reducing agent; 7-8 parts of other admixtures; the composite water reducing agent is an esterification product of graphene oxide and PCE, and other admixtures include water retaining agent and air entraining agent.

2. The C50 prestressed assembled box girder concrete according to claim 1, characterized in that: The weight ratio of the natural sand to the stone chips is 680:

120.

3. The C50 prestressed assembled box girder concrete according to claim 2, characterized in that: The weight ratio of the natural sand, limestone and natural river stone is 680:520:(400-500).

4. The C50 prestressed assembled box girder concrete according to claim 3, characterized in that: The weight ratio of the limestone to the natural river stone is 520:

450.

5. The C50 prestressed assembled box girder concrete according to claim 1, characterized in that: The weight ratio of the water retaining agent to the air entraining agent is 10:(1-2).

6. The C50 prestressed assembled box girder concrete according to claim 1, characterized in that: The preparation method of PCE comprises the following steps: mixing isopentanol polyoxyethylene ether, acrylic acid, sodium methacrylate sulfonate, an initiator, a chain transfer agent and water, controlling the initial reaction temperature to be 13-18°C, stirring the reaction for 3-5 hours, and then adjusting the pH in the system to be 6-8 to obtain PCE, wherein the weight ratio of isopentanol polyoxyethylene ether, acrylic acid and sodium methacrylate sulfonate is 1:(2.5-5):(0.2-0.4), and the weight ratio of isopentanol polyoxyethylene ether to the chain transfer agent is 1:(0.14-0.20).

7. The C50 prestressed assembled box girder concrete according to claim 6, characterized in that: In the preparation method of PCE, the weight ratio of prenol polyoxyethylene ether, acrylic acid and sodium methacrylic acid sulfonate is 1:4:0.

3.

8. The C50 prestressed assembled box girder concrete according to claim 7, characterized in that: In the preparation method of PCE, the weight ratio of isopentanol polyoxyethylene ether to the chain transfer agent is 1:0.

18.

9. A method for preparing C50 prestressed assembled box girder concrete according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the raw materials used, and stirring them evenly to obtain C50 prestressed assembled box beam concrete.